Association Between Subjective-Objective Discrepancy of Sleeping Time and Health-Related Quality of Life: A Community-Based Polysomnographic Study. Issue 4 (23rd May 2022) - Cho, Seo-Eun; Kang, Jae Myeong; Ko, Kwang-Pil; Lim, Weon-Jeong; Redline, Susan; Winkelman, John W.; Kang, Seung-Gul
Abstract : This is the largest study to date comprising 2540 community-based participants with polysomnographic data, examining sleep underestimation and overestimation in relation to quality of life. More than one-third of participants estimated their sleeping time significantly more or less than the objective polysomnographic sleeping time. These sleep underestimators and overestimators, compared with normoestimators, reported a poor quality of life (physical and mental aspects), suggesting a substantial prevalence and mental health comorbidity of subjective-objective discrepancy in sleep. ABSTRACT: Objective: This study aimed to investigate the existence of a difference in quality of life (QOL) between individuals with and without significant subjective-objective discrepancy (SOD) in total sleep time (TST). Methods: From the Sleep Heart Health Study 2, 2540 individuals who had completed polysomnography, a morning sleep survey, and the 36-item Short-Form Health Survey (SF-36) were included in the analyses. The participants were classified as normoestimators (estimation of TST <±60 minutes), underestimators (underestimation of TST ≥60 minutes), or overestimators (overestimation of TST ≥60 minutes). The standardized SF-36 QOL scores were compared among the three groups. An adjusted partial correlation analysis was conducted between SOD and QOL. Results: Of the 2540 participants, 1617 (63.7%), 433 (17.0%), and 490 (19.3%) were assigned to the normoestimator, underestimator, and overestimator groups, respectively. The bodily pain and social functioning components of the SF-36 score were significantly lower in the underestimators than in the normoestimators, whereas the physical functioning component was significantly lower in the overestimators than in the normoestimators. The absolute value of SOD in the TST showed a significant negative correlation with the physical and mental components of the SF-36. Conclusions: QOL was significantly better in the normoestimator than in the other groups and linearly correlated with the absolute value of SOD. This study suggests that a high prevalence of positive and negative sleep misperception in a community population can be a potential factor associated with poor QOL and potential comorbidities.